2022
DOI: 10.3389/fpls.2022.891775
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Traits, Nutritional, and Medicinal Component Quality of Polygonatum cyrtonema Hua and P. sibiricum Red.

Abstract: Polygonati rhizoma (Huangjing in Chinese) is a traditional and classic dual-purpose material used in food and medicine. Herbalists in China and Japan have noticed several different rhizome types in Huangjing with different qualities. Rhizome of Polygonatum cyrtonema Hua and P. sibiricum Red. is divided into five types: “Jitou-type” Polygonati rhizoma (JTPR), atypical “Jitou-type” Polygonati rhizoma (AJTPR), “Jiang-type” Polygonati rhizoma (JPR), “Cylinder-type” Polygonati rhizoma (CPR), and “Baiji-type” Polygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…These results demonstrated that the contents of sucrose and glucose were generally correlated with polysaccharide content. This was consistent with the regulation of sugar metabolism in rhizomes of P. cyrtonema Hua and P. sibiricum Red ( Hu et al, 2022 ). Sugars were involved in most of the metabolic and signaling pathways controlling plant growth and development, as well as the responses to abiotic stresses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results demonstrated that the contents of sucrose and glucose were generally correlated with polysaccharide content. This was consistent with the regulation of sugar metabolism in rhizomes of P. cyrtonema Hua and P. sibiricum Red ( Hu et al, 2022 ). Sugars were involved in most of the metabolic and signaling pathways controlling plant growth and development, as well as the responses to abiotic stresses.…”
Section: Discussionsupporting
confidence: 89%
“…Because rhizomes are the harvested targets, some studies have shown that rhizomes of P. cyrtonema Hua accumulated high content of polysaccharides, and unearthed several key genes involved in polysaccharide biosynthesis pathway from rhizomes at different ages by transcriptome sequencing ( Li et al, 2022 ). Besides, polysaccharide accumulation is also highly cultivar- and tissue-dependent ( Wang et al, 2019 ; Hu et al, 2022 ). For instance, Wang et al found that polysaccharide content was low in the leaf (1.62%) ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies have suggested that differences in the metabolic composition between varieties of the same species may result in species with different qualities and characteristics [ 7 , 8 ]. Some variation in the medicinal composition of Polygonatum species from different germplasms has been reported [ 9 , 10 ], and significant differences in the medicinal composition of Polygonatum species from the same germplasms have been found among different age sections and varying cultivation environments [ 11 ]. In recent years, the contents of total polysaccharides, total saponins, and some medicinal components, such as total flavonoids, have primarily been used as criteria to evaluate the quality of germplasms and age sections of Polygonatum species.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizoma Polygonati also helps in quenching thirst, moistening the lungs, and nourishing kidneys [ 17 , 18 ]. The extracts from P. cyrtonema and P. sibiricum offer health benefits such as antiaging, anticancer, and antitumor effects, immunity enhancement, reduced blood sugar and cholesterol levels, and reduced body weight [ 19 ]. Due to these health benefits, it has been enlisted as one of the key plants selected for the 100 billion Chinese medicine industry in Hunan Province.…”
Section: Introductionmentioning
confidence: 99%